Educational computer tool to teach the Morphofunctional Featuresof the Temporomandibular Joint - Alicia Herrera Forcelledo; Luis Alberto Lazo Herrera; Dianelys León Medina (Universidad Médica Pinareña, 2018)
Introduction: information and communication technologies allow the introduction of new paradigms in medical education considering student centeredapproaches, self-learning and the development of knowledge. Objective: to present a multimedia to teach the morphofunctional featuresof the temporomandibular jointfor first-academic year dentistry students. Method: a technological development study was carried out at Pinar del Rio University of Medical Sciences, during the period 2015-2016. Theoretical and empirical methods were applied. Validation of the product was conducted using Delphi method according to the criteria provided by eight (8) experts. The studied population was represented by 62 dentistry students and four (4) professors. Results: the multimedia consists of a presentation module that includes aspects related to content, exercises, materials to be discussed, images and videos. It received a positive assessment from the specialists regarding the different aspects comprising it, which issued "very adequate" criteria. Conclusions: a computer tool was approved to teach themorphofunctional featuresof the temporomandibular jointas a supporting material for the training of dentistry students. It was evaluated as excellent by experts and users, considering its generalization and relevance into the teaching-learning process.